I, me, mine - Harrison, George, 1943-2001 (Genesis Publications, 2017)
This is the closest we will come to George Harrison's autobiography. This new volume has been significantly updated since the 1980 original, it covers the full span of George Harrison's life and work--exploring his upbringing in Liverpool, the growth of Beatlemania, his love of India, gardening, and racing cars. It also presents 141 of George Harrison's songs, with lyrics handwritten and reproduced in facsimile, accompanied by his unique commentary. This new edition also includes more than 50 additional lyrics written for the Beatles and Harrison's solo albums. Included are written contributions from Olivia Harrision and Derek Taylor.